EHA research roadmap on hemoglobinopathies and thalassemia: an update - Iolascon, Achille; De Franceschi, Lucia; Muckenthaler, Martina; Taher, Ali; Rees, David; de Montalembert, Mariane; Rivella, Stefano; Eleftheriou, Androulla; Cappellini, Maria Domenica (HemaSphere, 2019)
The inherited disorders of hemoglobin, which include sickle cell disease and thalassemias, are the most common and widespread distributed monogenic disorders. Due to a selective advantage in malaria regions, these hemoglobin defects are particularly frequent in Africa, Asia, or in the Mediterranean areas, where malaria was endemic until the last century. In recent decades, the globalization of migration has contributed to generate multiethnic European societies. Due to migration from countries or regions with high hemoglobinopathy frequencies such as Africa, Middle East, or Asia, large numbers of patients with these disorders are living in almost every European country today. Furthermore, the numbers are increasing because of increasing refugee flows toward Europe. Additional requirements are the development of European recommendations and guidelines for diagnosis and effective therapeutic approaches. These, together with the advancement of clinical trials using new drugs and therapeutic procedures could ameliorate the quality of life of patients affected with these diseases and increase their life expectancy. Lastly, coordinated efforts should be made to develop diagnostic pathways for thalassemias and hemoglobinopathies, in order to plan interventions, including prenatal diagnosis and cure. For these reasons, the development of new tools to reliably diagnose anemias is urgently needed and fits well with the needs of personalized medicine. In the last 15 years, hematology research has made many big leaps forward. Our general aim will be to solve several hematologic problems using these new approaches. We expect that the development of such a diagnostic tool will improve timely diagnosis throughout Europe, especially in those countries where it is difficult to gain access to “classical” diagnostic tests.
Gesehen am 23.06.2020